THE EFFECTS OF ADDITIONAL EEL TAILED CATFISH (Paraplotosus albilabris) PROTEIN CONCENTRATE ON THE QUALITY OF KEMOJO CAKES - Desmita Sari; Dewita Dewita; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThe research was carried out to determine the effect of additional eel tailed catfish (Paraplotosus albilabris) protein concentrate on the quality of kemojo cakes. The method used was a Completely Randomized Design (CRD) non-factorial with four treatment levels, which was the additional eel tailed catfish protein concentrate into kemojo cakes: without eel tailed catfish protein concentrate (P0), 5% of eel tailed catfish protein concentrate (P1), 10% of eel tailed catfish protein concentrate (P2), 15% of eel tailed catfish protein concentrate (P3). The treatment was 3 replicated, so there were 12 units of experimental units. The result of the study based on organoleptic tested, it was indicated that an additional 10% of eel tailed catfish protein concentrate in kemojo cakes (P2) was the best treatment with the value of appearance 6.95, flavor 7.35, texture 7.32, and taste 7.24. Based on the proximate analysis that P2 treatment contained water, ash, protein, and fat content of 5,97%, 1.93%, 15.42%, and 11.28%, respectively. Keywords: kemojo cakes, eel tailed catfish, fish protein concentrate